Essential oil and furanosesquiterpenes from myrrh oleo-gum resin: a breakthrough in mosquito vector management - Eleonora Spinozzi; Marta Ferrati; Cecilia Baldassarri; Paolo Rossi; Guido Favia; Giorgio Cameli; Giovanni Benelli; Angelo Canale; Livia De Fazi; Roman Pavela; Luana Quassinti; Cristiano Giordani; et al. (Natural Products and Bioprospecting, 2025)
Abstract Mosquitoes (Diptera: Culicidae) are vectors of various pathogens of public health concern and replacing conventional insecticides remains a challenge. In this regard, natural products represent valuable sources of potential insecticidal compounds, thus increasingly attracting research interest. Commiphora myrrha (T.Nees) Engl. (Burseraceae) is a medicinal plant whose oleo-gum resin is used in food, cosmetics, fragrances, and pharmaceuticals. Herein, the larvicidal potential of its essential oil (EO) was assessed on four mosquito species (Aedes albopictus Skuse, Aedes aegypti L., Anopheles gambiae Giles and Anopheles stephensi Liston), with LC50 values ranging from 4.42 to 16.80 μg/mL. The bio-guided EO fractionation identified furanosesquiterpenes as the main larvicidal compounds. A GC–MS-driven untargeted metabolomic analysis revealed 32 affected metabolic pathways in treated larvae. The EO non-target toxicity on Daphnia magna Straus (LC50 = 4.51 μL/L) and its cytotoxicity on a human kidney cell line (HEK293) (IC50 of 14.38 μg/mL) were also assessed. This study shows the potential of plant products as innovative insecticidal agents and lays the groundwork for the possible exploitation of C. myrrha EO in sustainable approaches for mosquito management. Graphical Abstract